Demon Dentist - Walliams, David, 1971-; Ross, Tony. (New York, New York : Harper, an imprint of HarperCollinsPublishers, 2016)
Something strange is happening in Alfies town. Instead of shiny coins from the tooth fairy, kids are waking up to dead slugs, live spiders, and other icky, terrible things under their pillows. Who would do something so horrific? Theres nothing Alfie hates more than going to the dentist, but to solve this mystery, he may have to book a dreaded appointment...
Keywords: Dentists -- Juvenile fiction; Teeth -- Juvenile fiction; Single-parent families -- Juvenile fiction; Fear -- Juvenile fiction; Dentists -- Fiction; Teeth -- Fiction; Single-parent families -- Fiction; Fear -- Fiction; Juvenile humorous fiction